Holocaust in Alytus County in 1941 - Bubnys, Arūnas (Genocidas ir rezistencija, 2012)
Like other counties in Lithuania, the persecution and extermination of Jews in Alytus county can be divided into two phases. The first (the end of June–mid-July 1941) was dominated by political motives of persecution. Jews were often arrested, imprisoned, and shot to death, as were other former Communists, members of Komsomol, Soviet government officials or supporters. People of non- Jewish nationality (Lithuanians, Russians, Poles) were also persecuted for the same reason. The surviving lists of people detained and wanted by police show that in the first weeks of the Nazi occupation, the majority of people arrested in Alytus county because of pro-Soviet activities were, however, of Lithuanian ethnicity. What is particular about Alytus county is the more intense and wider persecution of Communists and Soviet activists than in other counties in Lithuania. By mid July 1941, 82 people in this category were shot in Alytus county under orders of the German military authority. Specific discriminatory measures applicable only to Jews included marking of the Jews (by making them wear the compulsory Star of David), prohibition to perform their religious rites publicly, provision of smaller food rations, prohibition to buy food products, and seizure of radio transmitters, motorcycles and bicycles. In the first phase, no massive or total Jewish genocide was enforced – women, children and old people were usually not arrested or shot.In the second phase (mid-July–mid-September 1941) the Jewish situation deteriorated. In the centres of rural districts where the numbers in the Jewish communities were large (for example, in Butrimonys), ghettos were set up and all Jews of the area were driven into the ghettos. This was when they started sending the detained groups of Jews to Alytus to be shot. In the middle of August 1941, the number of massacres of Jews increased considerably and by mid-September 1941, almost all of the Jews of Alytus county had been killed (except for the Jews of the Marcinkonys ghetto who were killed in November 1942 and individual Jews who managed to hide before shooting). On the basis of documents dated 1941, at least 6,165 Jews were murdered.Most of those who carried out the massacres were members of Obersturmführer Joachim Hamann’s ‘flying squad’ from Kaunas, local policemen and members of the auxiliary police, the so-called baltaraiščiai (they wore white armbands).More valuable items of Jewish property (golden jewellery, clocks, etc.) were appropriated by various German authorities, some of the property was appropriated by participants in the massacre, and what was left was sold to local inhabitants.
Keywords: German occupation; Holocaust; Alytus county